2019
DOI: 10.1515/ijamh-2018-0142
|View full text |Cite
|
Sign up to set email alerts
|

Literature review: nutritional factors influencing academic achievement in school age children

Abstract: Background and objective Adolescence is a transition period involving tremendous physical, psychological and cognitive growth. For appropriate growth of adolescents in these aspects, a correct quantity and quality of nourishment is required, as a lack of such nourishment among adolescents can lead to various degrees of malnutrition, which may have implications on their health as well as their academic achievements. Materials and methods This review examines the research topics around factors that influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Students' consumption of nutritious food has an impact on doing exams at school. They show better behavior (e.g., school attendance and complete assignments accurately), compared to students who do not consume nutritious food [27]. Other studies also report that obesity has been shown to have a poor impact on academic achievement [28][29][30].…”
Section: Effect Of Bmi On Pe Learning Outcomesmentioning
confidence: 99%
“…Students' consumption of nutritious food has an impact on doing exams at school. They show better behavior (e.g., school attendance and complete assignments accurately), compared to students who do not consume nutritious food [27]. Other studies also report that obesity has been shown to have a poor impact on academic achievement [28][29][30].…”
Section: Effect Of Bmi On Pe Learning Outcomesmentioning
confidence: 99%
“…Micronutrients like n-3 fatty acids, iron, iodine, zinc and B vitamins contribute to brain and cognitive development, memory and learning abilities (5) . Nutrient-rich diets positively influence cognitive function, concentration and academic performance (6) .…”
Section: The Importance Of Childhood Nutritionmentioning
confidence: 99%
“…Nutrient deficiencies and poor diets have consequences which include various psychological and cognitive challenges (to recap: having a negative impact on brain and cognitive development (5) , cognitive functioning, concentration, memory (6) , attention (12) , intelligence (13) , poor mental health (17) and lower mental well-being (18) , links to Attention Deficit Hyperactivity Disorder (14,15) and lower academic performance (6) ). Hence, healthcare and public health professionals need to consider how they assess these psychological and cognitive needs, and how any challenges associated with such needs are integrated into population based or targeted interventions.…”
Section: Key Learning Pointmentioning
confidence: 99%
“…Pendidikan yang baik mengarah pada peningkatan produktivitas, cara makan yang lebih baik dan penggunaan fasilitas perawatan kesehatan. [15][16] Merujuk pada hasil penelitian terkait hubungan tingkat konsumsi zat besi terhadap prestasi belajar remaja putri yang tercantum pada Tabel 8 bahwa tingkat konsumsi zat besi tidak berhubungan signifikan terhadap prestasi belajar Bahasa Indonesia nilai p = 0,096 (> 0,05), tingkat konsumsi zat besi tidak berhubungan signifikan terhadap prestasi belajar Matematika nilai p = 0,889 (> 0,05), tingkat konsumsi zat besi tidak berhubungan signifikan terhadap prestasi belajar Bahasa Inggris nilai p = 0,572 (> 0,05) dan tingkat konsumsi zat besi tidak berhubungan signifikan terhadap prestasi belajar Ilmu Pengetahuan Alam nilai p = 0,416 (> 0,05). Penelitian ini sejalan atas penelitian oleh Azzahra terkait mengetahui antara tingkat konsumsi zat besi (Fe) terhadap prestasi belajar pada remaja usia 10-19 tahun di SMA IT Daarul Rahman III bahwa tidak terdapat korelasi yang signifikan antara prestasi belajar dengan asupan zat besi (p value = 0,606).…”
Section: Pembahasanunclassified